How Diverse Are European Higher Education Systems? - Lepori , Benedetto; Wagner-Schuster, Daniel (International Higher Education, 2020)
A newly published report by the European Tertiary Education Register (ETER) project sheds new light on differences in the structure of European higher education systems. While the broad categorization in unitary vs. dual systems can still be applied, the distribution and differentiation of higher education within Europe is extremely heterogeneous in terms of distribution of students, subjects taught, and the extent of involvement in research.